A Case of Multiple Myeloma with Metachronous Chronic Myeloid Leukemia Treated Successfully with Bortezomib, Dexamethasone, and Dasatinib - Samer Alsidawi; Abhimanyu Ghose; Julianne Qualtieri; Neetu Radhakrishnan (Case Reports in Oncological Medicine)
The coexistence of multiple myeloma and chronic myeloid leukemia in a single patient is a very rare event that has been reported very infrequently in the literature. We report a case of a patient who developed chronic myeloid leukemia four years after his diagnosis with multiple myeloma. Historically, no link between the two malignancies has been identified. This synchronous existence complicates the treatment plan for these patients, and there is a lack of evidence on the best therapeutic approach. Our patient was successfully treated with a combination of bortezomib, dexamethasone, and dasatinib, which he tolerated well for eleven months until he eventually succumbed to cardiac complications and pulmonary hypertension leading to his death.